1969
DOI: 10.1002/app.1969.070131005
|View full text |Cite
|
Sign up to set email alerts
|

The pyrolysis of acrylic fiber in inert atmosphere. I. Reactions up to 400°C

Abstract: synopsisThe pyrolysis of acrylic fiber up to 400°C in an inert atmosphere at 1 ' and G°C/min was studied by means of thermogravimetric and differential thermal analysis. The exothermic reaction occurring at 180-300°C was shown to be due to the reaction of nitrile groups by comparing the extent of exotherm with the number of nitrile groups present, determined by infrared spectroscopy. In addition, results of single-fiber tensile measurements, density, and elemental analysis of the pyrolyzed fibers are interpret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
2

Year Published

1972
1972
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(19 citation statements)
references
References 13 publications
1
16
0
2
Order By: Relevance
“…The first peak (lower temperature side) of these triplets was assigned to the primary oxidation (including dehydrogenation) and cyclization reactions, with the second peak and the third peak (higher temperature side) assigned to the secondary oxidation reactions leading to the polymer chain scission which causes the evolution of HCN, CO 2 and CO. This is consistent with the experimental results by many workers [8,[19][20][21].…”
Section: Dsc Studiessupporting
confidence: 95%
“…The first peak (lower temperature side) of these triplets was assigned to the primary oxidation (including dehydrogenation) and cyclization reactions, with the second peak and the third peak (higher temperature side) assigned to the secondary oxidation reactions leading to the polymer chain scission which causes the evolution of HCN, CO 2 and CO. This is consistent with the experimental results by many workers [8,[19][20][21].…”
Section: Dsc Studiessupporting
confidence: 95%
“…It was supposed that the difference of exothermic behavior chiefly lay in the initial step. The exothermic peak at 288°C of PAN precursors was an important feature of programmed pyrolysis in an inert atmosphere, which was corresponded to the cyclization reaction of nitrile groups . The results indicated that the kinetics of exothermic reaction, which was believed to be related to the cyclization process of nitrile groups, was significantly modified by γ‐ray irradiation.…”
Section: Resultsmentioning
confidence: 92%
“…6 corresponds to the above assumption. G-band and D-band individually represent the resonances of carbon atoms in ordered and defective graphite structure [24,25]. The strong intensity and the narrow full width at half maximum (FWHM) of G-band signify the carbon film containing an abundance of ordered graphite structures, which could be attributed to highly ordered graphite layer developed early in the CVD process.…”
Section: Characterizations Of the Carbon Filmmentioning
confidence: 99%